2011
DOI: 10.1097/fpc.0b013e32834c0010
|View full text |Cite|
|
Sign up to set email alerts
|

The pharmacogenetics of metformin and its impact on plasma metformin steady-state levels and glycosylated hemoglobin A1c

Abstract: In a large cohort of type 2 diabetics, we either confirm or show for the first time: (a) an enormous (80-fold) variability in trough steady-state metformin plasma concentration, (b) OCT1 activity affects metformin steady-state pharmacokinetics, and (c) OCT1 genotype has a bearing on HbA1c during metformin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
212
3
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(235 citation statements)
references
References 43 publications
12
212
3
8
Order By: Relevance
“…As described above, neither the EGP nor any of the other variables were affected by the OCT1 allele status. This is in contrast to previous studies [12,13,38] and in agreement with others [14,39]. Most studies differ with respect to dosing of metformin (not only in amount but also single dose vs steady state) or participant population (type 2 diabetic patients vs healthy individuals) and may not be directly comparable.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As described above, neither the EGP nor any of the other variables were affected by the OCT1 allele status. This is in contrast to previous studies [12,13,38] and in agreement with others [14,39]. Most studies differ with respect to dosing of metformin (not only in amount but also single dose vs steady state) or participant population (type 2 diabetic patients vs healthy individuals) and may not be directly comparable.…”
Section: Discussionsupporting
confidence: 87%
“…Genetic variation in all of the above-mentioned transporters has been linked to altered pharmacokinetic and pharmacodynamic response to metformin [9]. In OCT1 (also known as SLC22A1), there are four known genetic variations (rs12208357 [R61C], rs34130495 [G401S], rs34059508 [G465R] and rs72552763 [M420del]), which encode an OCT1-transporter protein with reduced function and hence, have been linked to reduced-response metformin response in humans [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A possible direct effect of another medication, metformin, was also investigated. Metformin added to plasma ex vivo at a concentration of 1.2 μg/ml [25] did not affect cholesterol efflux (3.6±0.2% vs 3.5±0.5% p00.9).…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, genetic variation in the genes coding OCT1, OCT2, MATE1, and MATE2 (membrane transporters of metformin) have been linked to an altered pharmacodynamic and pharmacokinetic response to metformin; the genetic component to the variation in renal metformin clearance has been estimated to be approximately 90% [23]. Thus, the non-significant differences in the correlations between plasma steady-state concentrations of metformin with glycemic control and insulin resistance reported here most likely reflect a combination of variation in the renal excretion of metformin, volume of distribution, and in the bioavailability of the drug [20]. The lowering of blood glucose by metformin develops over at least 10 days [8] indicating that metformin has a long residence time in the liver or other effect compartments.…”
Section: Discussionmentioning
confidence: 74%
“…Accordingly, the suggested reason for such finding is the variation and inconsistent pharmacokinetics of metformin in diabetic patients. Mette et al demonstrate huge interindividual variations in trough steady-state metformin plasma levels in type 2 diabetics which may be attributed to the OCT1 transporter activity under trough steady-state conditions [20]. Moreover, Yasmin et al reported that there is no benefit from increased doses of metformin in females with PCOS, but reduction of insulin resistance is more significant in those patients with lower insulin sensitivity at baseline [21]; such condition is not clearly manifested in the present study due to relatively short duration of treatment, but at least impart support the idea of avoiding dose escalation without monitoring clinical improvement.…”
Section: Discussionmentioning
confidence: 99%